Critical Discourse Analysis of Micro and Macro Structures in Talks by Two Iranian Presidents at the United Nations General Assembly: A Socio-cognitive Perspective - Kayvan Shakoury; Veronika Makarova (Iranian Journal of Applied Language Studies, 2021)
This study analyzes official public talks by two Iranian presidents—Hassan Rouhani and Mahmoud Ahmadinejad—within the framework of Critical Discourse Studies (CDS). The study focuses on discoursal features in addresses of these presidents to the United Nations General Assembly at the micro-level (25 discursive devices) and the macro-level (positive self-representation and negative other-representation). The investigation attempts to determine whether significant differences existing in the micro and macro structures of these political discourses may be reflective of such factors as dissimilarities in political stance, world view and personal background. Combining quantitative and qualitative elements of analysis, the study demonstrates that consensus, illustration, hyperbole and polarization were used more frequently, whereas lexicalization and vagueness less frequently by Rouhani than by Ahmadinejad. At the semantic macro-level, Rouhani employed more positive self-representations and Ahmadinejad relied stronger on negative other-representation.   Results are interpreted within the CDS framework of political discourse.